ONLINE ENGLISH TEACHING BY USING GOOGLE CLASSROOM AND ITS CHALLENGES DURING COVID-19 PANDEMIC AT SMAN 1 GEDEG MOJOKERTO - Setiawan, Erik; Entusiastik, Entusiastik (Jurnal Pendidikan Bahasa Inggris Proficiency, 2022)
This reseach aimed 1) to know the teachers and students carry out online English teaching and learning, 2) to know the challenges of online English teaching and learning, and 3) to know about how the teacher and students solve the challenges during carrying out online English teaching and learning of analytical exposition text during the Covid-19 pandemic. This research used a qualitative approach. The researcher took 2 classes (IPA-1 & IPS-2) as sample. In the data collection technique, researcher used observation, interview, documentation, and questionnaire. The data analysis in this research used flow model data analysis by Miles and Huberman: checking the validity of the data with credibility, transferability, dependability, confirmability. The results showed that 1) The implementation of Online English teaching and learning was good, 2) Both of teachers had the same challenges such as time management, giving appropriate the material, and also collecting the task from the students, and 3) Both of the teachers had the same solution such as giving long time for the students to learn in Google Classroom, giving the additional material from the internet or gave the students opportunity to private chat by WhatsApp or Google Classroom, and giving the students longer time to collect the task till the following day. After finding the result, it is expected to be able to do better research as a reference to improve in educational research